Adaptive and sustainable design for building construction considering climate change - Hifza, Engr; Tariq, Hassan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The two most crucial factors that are constantly taken into account while developing or building any new infrastructure in this day and age are sustainability and resilience. In a similar manner, this project centers on the same idea of sustainability and resiliency in order to construct a 10-story structure that served the function of a multipurpose community center equipped with cutting edge technology and carefully selected construction materials in order to lessen the number of harmful emissions and to keep a balance in both the structural strength and the environment. The design process has involved choosing the primary building material, the type of construction used, the building plans, and the carbon footprints the selected building materials are generated. The building’s planned design also assessed for structural soundness, environmental sustainability, and resilience. The outcomes are compared to an existing structure in the same domain for the critical evaluation and effective decision-making. As a result, this compilation also includes a complete and in-depth analysis of how the suggested construction is more robust and sustainable. The preface also includes information on the building parts, such as the materials used to contrive the structural as well as the non-structural members. In the end, the suggested design is monitored based on its structural qualities to ensure its stability and resilience. In order to successfully propose a sustainable and resilient design for the building of a multipurpose 10-story community center, a comprehensive and optimal set of recommendations is provided.